1994
DOI: 10.1007/bf02639395
|View full text |Cite
|
Sign up to set email alerts
|

Colony isolation and secondary culture of fetal porcine hepatocytes on STO feeder cells

Abstract: SUMMARYThe secondary culture of non-transformed parenchymal hepatocytes has not been possible. STO feeder cell-dependent secondary cultures of fetal pig hepatocytes were established by colony isolation from primary cultures of 26-d fetal livers. The liver cells had the typical polygonal morphology of parenchymal hepatocytes. They also spontaneously differentiated to form small biliary canaliculi between individual cells or progressed further to large multicellular duct-like structures or cells undergoing gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…We have also shown that STO feeder cells will support the growth of pig fetal liver cells that differentiated into hepatocytes and ductal structures (Talbot et al, 1994b). We now show that adult pig intrahepatic bile duct cells can 'To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 69%
“…We have also shown that STO feeder cells will support the growth of pig fetal liver cells that differentiated into hepatocytes and ductal structures (Talbot et al, 1994b). We now show that adult pig intrahepatic bile duct cells can 'To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 69%
“…Spontaneous differentiation into endoderm-like cells has been previously shown in cultures derived from pig and bovine epiblasts (30,33), and colonies established from the porcine cells expressed ␣-fetoprotein, albumin, and ␤-fibrinogen mRNA (31,32) and may serve as a source for endodermspecific lines. Differentiation of ES cells which express endoderm-specific factors provides an experimental system for studying endoderm differentiation in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…It originated from the spontaneous differentiation of pig epiblast tissue and is therefore derived from pig embryonic stem cells [Talbot et al, 1993[Talbot et al, , 1994a. The cell line is also unique in its characteristic differentiation into two phenotypes that resemble fetal hepatocytes or fetal and adult bile duct epithelium [Talbot et al, 1994b]. The second of these phenotypes, bile duct epithelium, is manifested by a unique and striking in vitro morphological change, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these markers, the SIM mouse, thioguanine-and ouabain-resistant (STO) co-culture of numerous tissues of fetal and adult pigs (e.g., testis, kidney, pancreas, lung, brain, intestine, mammary gland, muscle, skin and blood) have not yielded cells that are similar in appearance or behavior to the PICM-19 cells. In contrast, the culture of fetal pig liver tissue [Talbot et al, 1994b] and adult pig liver tissue ] resulted in cell cultures that closely resembled the PICM-19 cells morphologically and biochemically. Thus, the PICM-19 cells appear to be bipotent liver stem cells with the ability to differentiate into monolayers of hepatocytes or multicellular ductal structures resembling bile duct epithelium.…”
Section: Introductionmentioning
confidence: 99%